Evaluation of Henes‐PCR assay for Mycobacterium detection in different clinical specimens from patients with or without tuberculosis‐associated HIV infection - Abanto, Segundo Moises Hernandez (J Clin Lab Anal, 2000)
The need for early diagnosis of tuberculosis, particularly in HIV‐infected patients, requires the development of diagnosis methods that have a high sensitivity and specificity, as does the nucleic acid‐based technology. With the purpose of improving the detection of mycobacterium in different clinical samples, we proposed and evaluated an assay based on nucleic acid‐amplification: heminested‐PCR (Henes‐PCR). The procedure was designed to identify Mycobacterium spp., M. tuberculosis complex (MTC), and M. avium complex (MAC), although it has the potential to include more primers for the identification of other species. Analytical and clinical evaluation of Henes‐PCR was performed by analysis of reference strains and 356 clinical specimens from 246 patients with pulmonary and meningitis tuberculosis and unrelated infections, including 142 HIV‐infected individuals. Ninety‐three percent (199) positive and 100% (143) negative results were obtained in specimens from patients with tuberculosis and non‐tuberculosis infection, respectively. The overall sensitivity of Henes‐PCR was 93.4%, specificity was 100%, positive and negative predictive values were 100 and 91.1%, respectively. Sensitivity and negative predictive value of Henes‐PCR were significantly higher than culture procedure for microscopy‐negative specimens. Even though frequency of HIV infection was higher in patients with tuberculosis, diagnostic parameters of Henes‐PCR were similar between HIV‐positive and HIV‐negative patients. MTB was identified in 194 (98%) specimens while MAC was detected in 5 (2%) specimens. These findings suggest that Henes‐PCR is a useful test for rapid detection of mycobacterium in clinically suspected cases of tuberculosis with smear‐negative results. J. Clin. Lab. Anal. 14:238–245, 2000. © 2000 Wiley‐Liss, Inc.